PEMBUATAN SARANA DAN PRASARANA DI LOKASI AIR TERJUN TATTIRI DI DESA BANAGAN KECAMATAN DAMPAL UTARA - Bayu Saputra; Debi Stefani; Abdul Wahid Safar; Moh Ma’ruf Bantilan; Dwi Purnomo (Makapande Mengabdi: Jurnal Ilmiah Pengabdian Kepada Masyarakat, 2025)
Tattiri Waterfall in Banagan Village, North Dampal District, is a natural destination with significant potential for development as a leading tourist attraction. However, limited facilities and infrastructure are a major obstacle to optimally utilizing this potential. This community service project aims to describe the efforts that have been and are being made to develop supporting infrastructure around the waterfall area, as well as to identify the obstacles encountered in this process. The method used is a qualitative approach, with data collection through interviews, field observations, and review of related documents. The results of the community service program show that there are initiatives from KKN students in the form of building signage and waste disposal areas. However, most of these facilities are still temporary and do not meet standards of comfort and safety for visitors. The main obstacles faced are limited budget and the lack of integrated planning based on local potential. Therefore, synergy is needed between the village government, the community, and other stakeholders in designing sustainable facilities and infrastructure development, so that the Tattiri Waterfall area can develop into a viable and competitive tourist destination.